Light emission in the unipolar regime of ambipolar organic field-effect transistors - Roelofs, W. S. Christian; Adriaans, Willem H.; Janssen, René A. J.; Kemerink, Martijn; Leeuw, Dago M. de (Advanced functional materials, 2013)
Light emission from ambipolar organic field-effect transistors (OFETs) is often observed when they are operated in the unipolar regime. This is unexpected, the light emission should be completely suppressed, because in the unipolar regime only one type of charge carrier is accumulated. Here, an electroluminescent diketopyrrolopyrrole copolymer is investigated. Local potential measurements by scanning Kelvin probe microscopy reveal a recombination position that is unstable in time due to the presence of injection barriers. The electroluminescence and electrical transport have been numerically analyzed. It is shown that the counterintuitive unipolar light emission is quantitatively explained by injection of minority carriers into deep tail states of the semiconductor. The density of the injected minority carriers is small. Hence they are relatively immobile and they recombine close the contact with accumulated majority carriers. The unipolar light output is characterized by a constant efficiency independent of gate bias. It is argued that light emission from OFETs predominantly originates from the unipolar regime when the charge transport is injection limited.